Air distributor for FCCU catalyst regenerator - COLVERT; JAMES H; LIONETTI; THOMAS A (1986)
An improved air ring for a regenerator in a fluid catalytic cracking process in which a baffle extends vertically downward from the air ring for a critical length. The baffle prevents catalyst erosion on the underside of the air ring and improves air distribution in the catalyst bed.